Probabilistic Analysis of the Human Vertebra Under Compressive Loading - Zulkifli, Ahmad@Manap; Ahmad Rasdan, Ismail; Mohd Azrul Hisham, Mohd Adib; Nasrul Hadi, Johari (2012)
The objective of this study is to determine the probability of injury of human crack vertebra condition subjected to compressive loading. The model has been used in this study was reconstructed from image processing and develop using SolidWorks. Three dimensional finite element model of human lumbar was conducted using Ansys software. In this work, all the model components were meshed using the tetrahedral solid element (SOLID186). In order to simplify the model, all the spinal components were modeled as an isotropic, elastic material and symmetry model. The model failure was occurred when the stress intensity factor (SIF) of the bone exceeds the fracture toughness. Biological structures, as well as a vertebra, exists a lot of related uncertainties and should not be solved by deterministic analysis. A Monte Carlo Simulation (MCS) technique was performed to conduct the probabilistic analysis using the built-in ANSYS parametric design language (APDL) modules. The results observed that the highest stress was found 2% on the adjacent pedicle to create the weakness area and probability of failure for cracked condition. Therefore, pedicle was become the most critical area to be emphasize. Despite, any flaws exist on the model such as crack will give a huge effect to the results especially fracture. Hence, the current study was very useful to investigate how the bone toughness and bone characteristics capable of sustained compressive loading in terms of the probabilistic approach.